Airport development projects in Thailand: a case study of Betong International Airport - Kiraphat Khianthongkul; Poowin Bunyavejchewin (Cogent Social Sciences, 2024)
Building new airports requires extensive investment. In principle, airport development projects should be well-planned and thoughtfully designed. Despite this, the Department of Airports (DOA), a part of the Thai bureaucracy, has allegedly continued constructing remote airports that do not appear economically viable. The reasons for these unexplained projects have also been studied. Political, economic, social, technological, legal, and ecological analyses were used to explore and evaluate the macroenvironmental factors that influence the DOA in initiating project decisions. The newly opened Betong International Airport in the southernmost district of Yala Province was used as a case study. By examining the macroenvironmental setting, the findings showed that the DOA’s bureaucratic culture was the key condition responsible for the flawed and defective layout of the nation’s southernmost airport. This, in turn, made Betong International Airport economically unfeasible for local airlines servicing routes from Betong to other destinations.